Critical Thinking Skills and Sustainability Conciousness of Students for The Implementation Education for Sustainable Development - E. F. D. Sobari; H. Hernani; T. R. Ramalis (Universitas Negeri Yogyakarta, 2022)
The study aimed to describe the critical thinking skills and sustainability consciousness of students of one junior high school in Bandung using an E-module of environmental pollution containing education for sustainability development (ESD). The research used descriptive qualitative and quantitative methods. This study involved 32 participants using a research instrument in the form of critical thinking skills essay questions that contained sustainability consciousness (ESD) with a total of 12 questions. The study indicated that critical thinking skills reach the highest score on the indicator of building basic skills of 78.1% and the lowest score on the concluding indicator of 64.8%. The average score of students' critical thinking skills was 74.4%, which showed the level of students' critical thinking skills in the adequate category. Meanwhile, the sustainability consciousness components showed that the sustainable knowledge, sustainable attitude, and sustainable behavior were constructed with percentages of 82.1%; 79.5%; and 77.8% indicating that the average students’ sustainability consciousness was 79.8% in the good category